The Dance Factory, Newtown, Johannesburg a site of resistance - Ginslov, Jeannette (Rhodes University, Faculty of Humanities, Department of Drama, 1998)
This mini thesis proposes that the Dance Factory in Ne'Ntown, Johannesburg, is a site of resistance. Its source and motivation are the personal, artistic and socio-poIiticaI sites ofresistance to mainstream forms of dance with nationalistic tendencies and to dominant ideological hegemonies that enforced apartheid or nationalism. Therefore, these sites or resistance are examined prior to and after the democratisation of South African culture. An analysis of the dances choreographed in this period of transition and changing hegemonies reveal shifts of resistance. These are traced within the development of the Dance Factory. Chapter one explores the notion of resistance as a form of power and the notion of site, where the operations of power evoke resistance. Three sites of resistance within South African dance culture are identified and examined. These are the Dance Factory, the artistic site of dance and the site of the dancing body. The chapter reveals the development of these sites in a changed culture and notes a re-orientation of resistance within dance, namely Afro-fusion, and the subsequent development and emergence of 'alternative' sites of resistance. These reveal new expressionistic tendencies, body politics and the feminist strategies of 'new poetics' and 'ecriture feminine'. The codified mainstream forms of dance, subject to nationalistic strategies of dassicism and its inherent Iogocentricity are challenged and destabilised by the emergence of these altemative resistant forms of dance. Chapter two examines the artistic policies of the Nationalist Govemment, the African National Congress and the Dance Factory from 1983-1997. It notes the effects of the changes in the artistic policies on sites of resistance in dance, performed at the Dance Factory. The chapter desaibes the development of the Dance Factory, its policies of diversification as a strategy of resistance, its promotion of praxis, its resistance to nationalism and the ramifications thereof. It also explores the effects of a governmentalisation of culture and the role of the organic intellectual within the Dance Factory. An analysis of the alternative dance work 'Torso-Tongue" in chapter three furthers the argument that the Dance Factory maintains and encourages the changing sites of resistance in dance. This analysis demonstrates the resistant aspects of dance as discussed in chapter one and thereby confirms the aims and missions of the Dance Factory. The thesis examines the role of the Dance Factory as it develops, nurtures and responds to the shifts in resistance and changes in culture and dance. Most importantly the thesis exposes the resistance to and the effects of an imposition of a nationalistic ideology on dance. The resultant resistance to this form of domination is explored in dance within the site of the Dance Factory, thus supporting the premise that the Dance Factory is a site of resistance.
Keywords: Dance factory; Dance -- Political aspects -- South Africa